2022
DOI: 10.1158/1078-0432.ccr-21-2649
|View full text |Cite
|
Sign up to set email alerts
|

Association of PD-1/PD-L1 Co-location with Immunotherapy Outcomes in Non–Small Cell Lung Cancer

Abstract: Purpose: Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) interaction suppresses local T-cell responses and promotes peripheral tolerance. In the current study, we focus on PD-1/PD-L1 co-location as a surrogate for this interaction and assess its association with immunotherapy outcomes in patients with non–small cell lung cancer (NSCLC). Experimental Design: Pretreatment biopsies from a retrospective c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…CD68 is the classic tumor-associated macrophage marker, a double-edged sword in antitumor immunity. Previous studies revealed CD68+ macrophages were the predominant immune cell type expressing PD-L1 [38,39].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…CD68 is the classic tumor-associated macrophage marker, a double-edged sword in antitumor immunity. Previous studies revealed CD68+ macrophages were the predominant immune cell type expressing PD-L1 [38,39].…”
Section: Discussionmentioning
confidence: 92%
“…CD68 is the classic tumor‐associated macrophage marker, a double‐edged sword in antitumor immunity. Previous studies revealed CD68+ macrophages were the predominant immune cell type expressing PD‐L1 [ 38 , 39 ]. A high level of PD‐L1 in macrophages was significantly correlated with a high level of PD‐L1 expression in tumor cells and CD8+ T cells infiltration, indicating an inflamed TME phenotype [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial profiling technologies are powerful tool to analyze immune cell typing, immune activation and therapeutic options ( 33 , 34 ). Likewise, co-location of immuno-biomarkers can be used as prognostic indicators ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study recently published in Clinical Cancer Research , titled “Association of PD‐1/PD‐L1 Co‐location with Immunotherapy Outcomes in Non‐Small Cell Lung Cancer,” Gavrielatou et al 11 assessed the co‐location of PD‐1 and PD‐L1 on a retrospective cohort of 154 advanced NSCLC patients treated with immune checkpoint inhibitor. Expression of PD‐1 and PD‐L1 was detected by multiplex quantitative immunofluorescence.…”
mentioning
confidence: 99%